2023
DOI: 10.3390/ph16020206
|View full text |Cite
|
Sign up to set email alerts
|

Role and Mechanisms of Phytochemicals in Hair Growth and Health

Abstract: Hair health is associated with personal distress and psychological well-being. Even though hair loss (alopecia) does not affect humans’ biological health, it affects an individual’s social well-being. So, treatment for hair problems and improving hair health are obligatory. Several pharmacological and cosmeceutical treatment procedures are available to manage hair loss and promote growth. Several factors associated with hair health include genetics, disease or disorder, drugs, lifestyle, chemical exposure, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 145 publications
0
16
1
1
Order By: Relevance
“…Studies on hair growth-promoting activities of phytochemicals have proved effective in managing hair loss. 21 The use of such naturally derived ingredients eliminates the side-effects, while providing the required therapeutic benefit. Likewise, it was observed that our test treatment-an ayurvedic hair oil, proved to work well in the management of hair fall.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on hair growth-promoting activities of phytochemicals have proved effective in managing hair loss. 21 The use of such naturally derived ingredients eliminates the side-effects, while providing the required therapeutic benefit. Likewise, it was observed that our test treatment-an ayurvedic hair oil, proved to work well in the management of hair fall.…”
Section: Discussionmentioning
confidence: 99%
“…Although phytochemicals have potential for treating alopecia, they have several limitations, including the limited availability of clinical evidence, varying levels of effectiveness, and slow appearance of results. In addition, phytochemical treatments are less effective for individuals with more severe hair loss 145 . Controlled shampoo use and lifestyle modifications are more direct approaches to the prevention and treatment of hair loss than phytochemical use.…”
Section: New Treatment Strategies For Hair Lossmentioning
confidence: 99%
“…Hasil pada Tabel 2 menunjukkan gejala klinis dan perubahan patologis keracunan Se cukup bervariasi. Gejala klinis dapat berupa kekurusan, penurunan penampilan, kerusakan dan pertumbuhan abnormal kuku, kerontokan rambut, alopecia, gangguan reproduksi, dyspnea, sianosis dan kematian mendadak (Kim, 2001;Kesika et al, 2023). Sedangkan perubahan patologis ditunjukkan dengan adanya nekrosis miokardium, nekrosis otot skelet, edema paru paru, hidrotoraks, hidroperikardium, edema abdominal dan hemoragi mukosa usus (McKenzie & Al-Dissi, 2017).…”
Section: Toksisitas Selenium Dan Vitamin E Pada Ternak Ruminansiaunclassified